In - situ Electrochemical Synthesis, Microscopic and Spectroscopic Characterisations of Electroactive poly(2,5-dimethoxyaniline) – Multi-Walled Carbon Nanotubes Composite Films in Neutral Media - Masikini, Milua; Mailu, Stephen N.; Tsegaye, Abebaw; Ikpo, Chinwe O.; Njomo, NJagi; Waryo, Tesfaye T.; Baker, Priscilla G. L.; Iwuoha, Emmanuel I. (International Journal of ELECTROCHEMICAL SCIENCE, 2014)
Poly(2,5- dimethoxyaniline)-multi-wall carbon nanotubes (PDMA-MWCNT) nanocomposite films were synthesised by in –situ electrochemical polymerisation. The films were characterised by cyclic voltammetry (CV), ultra–visible spectroscopy (Uv-vis), spectroelectrochemistry, fourier transform infra-red spectroscopy (FTIR) and scanning electron microscopy (SEM). For comparison, Poly(2,5- dimethoxyaniline) without carbon nanotubes (PDMA) was also synthesised. The UV-vis indicated that the films were still in their salt form (doped) and the energy band gap shows the films were semiconductors. The spectroelectrochemistry reveals that the band at 470 nm was found to be bathochromically shifted to 500 nm for potentials below +150 mV (form -750 to 0 mV versus Ag/AgCl) and was found to decrease shifted toward lower energy (red shift or bathochromic shift) with apparition of a new band at around 800 nm with increasing potentials (from +150 to +750 mV versus Ag/AgCl). FTIR confirmed the incorporation of MWCNT into polymer matrix. SEM micrograhs of PDMA and PDMA-MWCNT composite films showed net structure of ‘Flower-like’microfiber with diameters ~ 200 nm. The cyclic voltammetry showed two distinctive peaks, which indicates that the films were electoractives in phosphate buffer saline (PBS).
Keywords: Electrochemical Synthesis